In vitro osteoclast formation and resorption of silicon‐substituted hydroxyapatite ceramics. Issue 10 (22nd April 2015) - Friederichs, Robert J.; Brooks, Roger A.; Ueda, Masato; Best, Serena M.
ABSTRACT Materials that participate in bone remodeling at the implant/tissue interface represent a modern tissue engineering approach with the aim of balancing implant resorption and nascent tissue formation. Silicon‐substituted hydroxyapatite (SiHA) ceramics are capable of stimulating new bone formation, but little is known about their interaction with osteoclasts (OC). The effects of soluble silicate and SiHA on OCs were investigated in this study. Soluble silicate below 500 μM did not stimulate cell metabolism at 4 days or alter resorption area at 7 days on calcium phosphate discs. On sintered ceramics, OC numbers were similar on HA, Si0.3HA (0.5 wt % Si) and Si0.5HA (1.2 wt % Si) after 21 days in vitro, but actin ring sealing zone morphology on SiHA resembled that commonly found on bone or on carbonate‐substituted hydroxyapatite (CHA). Smaller and thicker actin rings on SiHA as compared to HA were probably the result of altered surface chemistry and solubility differences. The more stable sealing zones and increased lattice solubility likely contributed to increased individual pit volumes observed on Si0.5HA. The delayed formation of OCs on Si0.5HA (lower numbers at day 14) excludes earlier differentiation as a possible mechanism of increased individual OC pit volumes at later times (day 21). Materials characterization of Si containing biomaterials remains paramount as the Si type and amounts can subsequently impact downstream OC behaviour in a complex manner. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3312–3322, 2015.